English and Welsh civil and social justice panel survey: waves 1-2, 2010-2012 (UK Data Service, 2015)
The English and Welsh Civil and Social Justice Panel Survey (CSJPS) collects data relating to people’s experiences of civil justice (or ‘justiciable’) problems and the strategies they used to resolve them. The survey is a substantial development of the English and Welsh Civil and Social Justice Survey (CSJS), which was first conducted in 2001, then again in 2004, and on a continuous basis between 2006 and 2009. Respondents to the first wave of the CSJPS, conducted between June and October 2010, were asked about the experience of problems in each of 15 distinct civil justice problem categories: consumer; employment; neighbours; owned housing; rented housing; money; debt; welfare benefits; divorce; problems ancillary to relationship breakdown; domestic violence; education; care proceedings; personal injury, and clinical negligence. For up to three problems (selected at random, if more than three problems had been experienced), respondents were asked about disputants, problem resolution strategies, advisers consulted, formal dispute resolution processes, how and when problems concluded, the causes and consequences of problems, understanding of rights, and regrets. For one (random) problem, respondents were also asked for detailed information about the steps they had taken to resolve it. Extensive Demographic and household details were also collected. The fieldwork for the second wave of the CSJPS was carried from winter 2011 (18 months after the Wave 1). The survey was broadly similar to Wave 1. Ongoing problems at the time of the wave 1 interview were also revisited at wave 2, with further details set out in the technical report and questionnaire.